2010
DOI: 10.2165/11531840-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Veno-Occlusive Disease

Abstract: Hepatic veno-occlusive disease (VOD) is a major manifestation of liver toxicity associated with conventional and high-dose chemotherapy in children affected by hematologic malignancies and certain solid tumors. Clinically, patients present with jaundice, painful hepatomegaly, and fluid retention, which may evolve into multi-organ failure, a hallmark of severe disease. The pathogenesis is complex and not completely understood, but the damage to sinusoidal endothelium, typically caused by toxic metabolites relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 76 publications
(42 reference statements)
1
25
0
5
Order By: Relevance
“…More severe reactions and systemic anaphylaxis may be life-threatening (Cefalo et al, 2010). It is possible that carboplatin HSRs are not always recognized.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…More severe reactions and systemic anaphylaxis may be life-threatening (Cefalo et al, 2010). It is possible that carboplatin HSRs are not always recognized.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Some authors have tried to predict HSRs by using skin testing (Zanotti et al, 2001; Cefalo et al, 2010). Zanotti et al (2001) developed a skin-test protocol for adult patients with gynecological malignancies and first demonstrated that skin testing for carboplatin made it possible to identify patients at risk for HSRs with a 99% negative predictive value.…”
Section: Pathophysiologymentioning
confidence: 99%
“…It is reported more commonly with myeloablative chemotherapy and total body irradiation prior to allogeneic bone marrow transplantation (Cefalo et al 2010 ). HVOD is characterized by necrosis of the hepatocytes, sinusoidal fi brosis, and occlusion of the hepatic venules with subsequent hepatic congestion (Robinson et al 2011 ).…”
Section: 3mentioning
confidence: 99%
“…The clinical presentation includes jaundice, tender hepatomegaly, and unexplained weight gain with or without ascites. Liver enzymes may be abnormal and thrombocytopenia may develop (Cefalo et al 2010 ;Richardson and Guinan 1999 ).…”
Section: 3mentioning
confidence: 99%
“…The underlying pathogenesis is complex and thought to involve toxic injury to sinusoidal endothelial cells 1. Histologic confirmation with liver biopsy is the gold standard for diagnosis; however, due to the procedural risk and invasive nature of a biopsy the majority of cases are diagnosed clinically.…”
mentioning
confidence: 99%